Depression of lead-activated sphalerite by pyrite via galvanic interactions: Implications to the selective flotation of complex sulfide ores - Aikawa, Kosei; Ito, Mayumi; Segawa, Tatsuya; Jeon, Sanghee; Park, Ilhwan; Tabelin, Carlito Baltazar; Hiroyoshi, Naoki (Minerals engineering, 2020)
[Display omitted] •Pyrite depresses the floatability of lead-activated sphalerite.•Galvanic interactions between pyrite and lead-activated sphalerite occur.•Galvanic interactions cause the dissolution of activated PbS layer on sphalerite.•Dissolved Pb creates hydrophilic Pb(OH)2 layer on the surface of sphalerite. Complex sulfide ores are typically mixtures of various sulfide minerals like sphalerite (ZnS), chalcopyrite (CuFeS2), galena (PbS), pyrite (FeS2), and barite (BaSO4) and processed by selective flotation to recover target-sulfide minerals like chalcopyrite and sphalerite. Some complex sulfide ores, however, contain anglesite (PbSO4), a mineral with relatively high solubility, that complicates selective flotation because its dissolution releases Pb2+, which ‘activates’ co-existing sulfide minerals (e.g., ZnS). Because both target and non-target sulfide minerals are recovered when flotation is non-selective, another flotation stage to recover target minerals in froth products is required. Aside from anglesite, co-existing gangue sulfide minerals like pyrite also complicate selective flotation because of their strong effects on the floatability of target-sulfide minerals via electrochemical interactions. In this study, the effects of pyrite on the floatability of lead-activated sphalerite were investigated using flotation tests and electrochemical techniques coupled with contact angle measurements. Moreover, factors important to lead-activated sphalerite floatability were elucidated in detail using dissolution experiments and X-ray photoelectron spectroscopy (XPS). Finally, a mechanism for lead-activated sphalerite depression by pyrite is proposed.